Survival in interstitial pneumonia with features of autoimmune disease: A comparison of proposed criteria. Issue 10 (October 2015) - Assayag, Deborah; Kim, Eunice J.; Elicker, Brett M.; Jones, Kirk D.; Golden, Jeffrey A.; King, Talmadge E.; Koth, Laura L.; Shum, Anthony K.; Wolters, Paul J.; Collard, Harold R.; Lee, Joyce S.
Abstract: Background: Some patients with chronic fibrosing interstitial pneumonia (IP) have clinical, serological, and morphological features suggestive of, but not diagnostic for, a connective tissue disease. Several names and diagnostic criteria for this entity have been proposed. The objective of this study was to compare the clinical characteristics and behavior of each of the proposed diagnostic criteria. Methods: Patients with chronic fibrosing IP were identified from an ongoing, longitudinal cohort. Four published diagnostic criteria for what we generically label as "IP with features of autoimmunity" were applied to all patients to identify four unique cohorts (Kinder, Vij, Corte, and Fischer). Kaplan–Meier survival functions compared differences in survival in each cohort between patients meeting and not meeting criteria. Unadjusted and adjusted Cox proportional hazard regression models identified predictors of survival. Results: The study cohort included 119 patients, 40% of whom were female. The mean age was 65.5 years. There was overlap between the four different criteria, identifying patients with similar clinical characteristics. Interstitial pneumonia patients with features of autoimmunity tended to have improved survival compared to those without these features (p-value range 0.03–0.10) on univariate analysis. After adjusting for disease severity using the gender-age-physiology score, only the Corte criteria was an independent predictor of survival (p-value 0.04). Conclusion: Interstitial pneumonia with features of autoimmunity may be associated with improved survival compared to those patients without these features depending on which criteria is used to define the population. These data support the efforts being made to standardize the definition. Highlights: Existing criteria for autoimmune-featured IP identify similar but distinct cohorts. IP patients with features of autoimmunity may have improved survival. Standardization of the definition will be important moving forward.